2015
DOI: 10.1002/chem.201500311
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Active Site Model of the [NiFeSe] Hydrogenase

Abstract: A dinuclear synthetic model of the [NiFeSe] hydrogenase active site and a structural, spectroscopic and electrochemical analysis of this complex is reported. [NiFe(‘S2Se2’)(CO)3] (H2‘S2Se2’=1,2-bis(2-thiabutyl-3,3-dimethyl-4-selenol)benzene) has been synthesized by reacting the nickel selenolate complex [Ni(‘S2Se2’)] with [Fe(CO)3bda] (bda=benzylideneacetone). X-ray crystal structure analysis confirms that [NiFe(‘S2Se2’)(CO)3] mimics the key structural features of the enzyme active site, including a doubly bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 89 publications
2
51
0
Order By: Relevance
“…The work presented herein reveals clear effects of Fe II –Se over Fe II –S coordination on the electrochemical properties of isostructural tetrahedral Fe II complexes, as the Fe II → Fe III oxidation for 2 occurs at a lower potential than that of 1 (Figure , Table ). This observation implies that the Se‐containing ligand has a stronger electron‐donation ability than the S‐containing one, in agreement with the smaller electronegativity of Se over S. It should be noted that the above trend in electron‐donation ability has been observed in a host of transition‐metal complexes, including synthetic analogues of the active sites of FeFe and NiFeSe hydrogenases, in which thiolates are replaced by selenolates…”
Section: Resultssupporting
confidence: 59%
“…The work presented herein reveals clear effects of Fe II –Se over Fe II –S coordination on the electrochemical properties of isostructural tetrahedral Fe II complexes, as the Fe II → Fe III oxidation for 2 occurs at a lower potential than that of 1 (Figure , Table ). This observation implies that the Se‐containing ligand has a stronger electron‐donation ability than the S‐containing one, in agreement with the smaller electronegativity of Se over S. It should be noted that the above trend in electron‐donation ability has been observed in a host of transition‐metal complexes, including synthetic analogues of the active sites of FeFe and NiFeSe hydrogenases, in which thiolates are replaced by selenolates…”
Section: Resultssupporting
confidence: 59%
“…Recent evidence has suggested that conversion from Ni-A to Ni-B is also assisted by the oxygenation of one of the bridging S-atoms. 55,56 The chemical role of selenocysteine in protecting the hydrogenase from oxidative damage is currently under investigation, 57 58 The O 2 tolerance may be a result of the easier oxidation and reduction of Se compared to S. 59 Due to the extreme O 2 sensitivity of many hydrogenases, engineering the enzymes to reduce protons and O 2 simultaneously is a significant challenge, 60,61 and currently Peters and coworkers showed in 2012 that a [NiFe] hydrogenase from Thiocapsa roseopersicina covalently linked to a Ru dye was able to photocatalytically reduce protons under aerobic conditions in the presence of the soluble redox mediator methyl viologen (MV) and a sacrificial electron donor. 42 The [NiFeSe] hydrogenase is a subclass of the [NiFe] hydrogenase that is highly active for proton reduction in the presence of H 2 and illustrates a promising degree of tolerance to O 2 .…”
Section: This Journal Is © the Royal Society Of Chemistry 2012mentioning
confidence: 99%
“…The combination of Se with a metal has already been described, with nickel as the metal (2). In that case, the presence of Se in the active site of hydrogenase enhanced its enzymatic property.…”
mentioning
confidence: 92%